Investimentos estruturantes e desigualdades regionais na Região Nordeste - Luiz Carlos de Santana Ribeiro (2015)
This dissertation aims to evaluate the long-run regional impacts from the implementation of three oil refineries announced for the Brazilian's Northeast region. Despite the Brazilian regional inequalities have been reduced in recent years, the Northeast is still the most unequal region in the country. Thus, the extent to which the construction of these three refineries could contribute to reducing regional inequalities? Or, would there be an increase in intra-regional inequalities, since the investments would be concentrated in three states? In an attempt to answer these questions, a dynamic and interregional Computable General Equilibrium (CGE) model was developed, with micro-regional specification to the interest's areas of the study. This model, called B-NORIM, consists of 28 regions in the Northeast and the rest of Brazil and 30 economic sectors. We opted for the evaluation of investments in oil refining due to linkage and attraction power that this segment has on other sectors of the economy. The theoretical discussion of this dissertation is part of Regional Science's scope, especially in perrouxian Growth Poles theory and the importance given by Hirschman to sectoral linkages. On the other hand, the empirical approach is based on multisectoral simulation models in general equilibrium, input-output and CGE. The main results of the refinery investments' simulations in NE indicate positive impacts in all regions. The impact on regional GDP between 2006 and 2027, would bring an additional effect to the micro-regions of Rosário-MA, Fortaleza-CE and Suape-PE, refiniries' locations, of 5.79%, 0.05% and 1.42%, respectively. However, the implementation of these three refineries would cause an increase in intra-regional inequalities, given the concentration of the benefits in these regions and more developed regions. On the other hand, in the long run, these investments could contribute to the Northeast increased their relative share in the Brazilian GDP.